Translocator protein-mediated pharmacology of cholesterol transport and steroidogenesis. (15th June 2015) - Papadopoulos, Vassilios; Aghazadeh, Yasaman; Fan, Jinjiang; Campioli, Enrico; Zirkin, Barry; Midzak, Andrew
Highlights: Historical perspective on pharmacological targeting of TSPO in steroidogenesis. Targeting mitochondrial transduceosome for control of steroidogenesis. Review of recent genetic engineering work targeting transduceosome components. Abstract: Steroidogenesis begins with cholesterol transfer into mitochondria through the transduceosome, a complex composed of cytosolic proteins that include steroidogenesis acute regulatory protein (STAR), 14-3-3 adaptor proteins, and the outer mitochondrial membrane proteins Translocator Protein (TSPO) and Voltage-Dependent Anion Channel (VDAC). TSPO is a drug- and cholesterol-binding protein found at particularly high levels in steroid synthesizing cells. Its aberrant expression has been linked to cancer, neurodegeneration, neuropsychiatric disorders and primary hypogonadism. Brain steroids serve as local regulators of neural development and excitability. Reduced levels of these steroids have been linked to depression, anxiety and neurodegeneration. Reduced serum testosterone is common among subfertile young men and aging men, and is associated with depression, metabolic syndrome and reduced sexual function. Although testosterone-replacement therapy is available, there are undesired side-effects. TSPO drug ligands have been proposed as therapeutic agents to regulate steroid levels in the brain and testis.